THE HARMONIZATION OF TRADITION AND SUSTAINABILITY: COSTUME DESIGN IN KALPATARU CONTEMPORARY DANCE AT THE KITAPOLENG FOUNDATION - Diantari, Yuni (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2025)
This study aims to examine the role of Kalpataru contemporary dance costume design at the Kitapoleng Foundation as a medium of expression that integrates Balinese cultural heritage with the principles of sustainability and design innovation. The focus is on symbolism, sustainable materials, and the contribution of costumes to the narrative of the performance. This study uses a descriptive qualitative approach with case studies. Data was collected through semi-structured interviews with the choreographer, designer, and founder of Kitapoleng; observation of performances at IFEX 2024; and visual documentation. Analysis was conducted using data reduction, thematic categorization, and source triangulation methods. The woven ental fabric costumes combine symbols of tradition and sustainability. Design innovations include reinterpretations of Legong headdresses and badong accessories. The costumes reinforce the Kalpataru philosophy of the “tree of life” and increase the audience's understanding of ecological and cultural issues. Cultural negotiation emerges in the reinterpretation of tradition. The results of this research enrich performance studies through the perspective of sustainability. In practical terms, this research offers a model of collaboration between artists and craftsmen as an environmentally friendly design practice based on local culture. These findings also have implications for arts education strategies and the strengthening of Indonesian performing arts in the global discourse on sustainability.